2019
DOI: 10.1128/mbio.01448-19
|View full text |Cite
|
Sign up to set email alerts
|

Cell Shape and Antibiotic Resistance Are Maintained by the Activity of Multiple FtsW and RodA Enzymes in Listeria monocytogenes

Abstract: Rod-shaped bacteria have two modes of peptidoglycan synthesis: lateral synthesis and synthesis at the cell division site. These two processes are controlled by two macromolecular protein complexes, the elongasome and divisome. Recently, it has been shown that the Bacillus subtilis RodA protein, which forms part of the elongasome, has peptidoglycan glycosyltransferase activity. The cell division-specific RodA homolog FtsW fulfils a similar role at the divisome. The human pathogen Listeria monocytogenes carries … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 67 publications
3
24
0
Order By: Relevance
“…FtsW is essential in most organisms containing a single copy of this gene. Depletion of FtsW in rod-shaped bacteria leads to a block in cell division and formation of elongated cells [59][60][61] . In the polyploid spherical cyanobacterium Synechocystis sp.…”
Section: Discussionmentioning
confidence: 99%
“…FtsW is essential in most organisms containing a single copy of this gene. Depletion of FtsW in rod-shaped bacteria leads to a block in cell division and formation of elongated cells [59][60][61] . In the polyploid spherical cyanobacterium Synechocystis sp.…”
Section: Discussionmentioning
confidence: 99%
“…The elongation of L. monocytogenes cells by UA-CS NPs in the present study might be due to the inhibition of cell division. The genome of L. monocytogenes contains the lmo1071 gene that encodes the FtSW protein, which is responsible for cell division; when the gene is mutated cells become elongated [79]. Hence, in the presence of UA-CS NPs, the elongation of cells might be due to the inhibition of cell division.…”
Section: Effect Of Ua-cs Nps On Cell Morphologymentioning
confidence: 99%
“…I am particularly intrigued with this idea of environment sensing. A recent study revealed that the genome of the intracellular pathogen Listeria monocytogenes encodes three RodA (RodA1, RodA2, RodA3) and two FtsW (FtsW1, FtsW2) paralogs (Rismondo, Halbedel, & Grundling, ). Deficiencies in some of these proteins result in changes in shape and antibiotic resistance, therefore displaying capacity for a functional interchange in the laboratory medium.…”
Section: Gain and Loss Of Pg Enzymes In Intracellular Pathogens: Oblimentioning
confidence: 99%